Design and Synthesis of Vanadium‐Titanium‐Incorporated Mesoporous Silica Catalysts for the Oxidative Dehydrogenation of Propane. Issue 13 (30th March 2022) - Xie, Zean; Zhang, Xiao; Zhao, Jin; Wang, Lu; Fan, Xiaoqiang; Kong, Lian; Song, Yangyang; Zhao, Zhen
Abstract: A series of vanadium and titanium‐incorporated mesostructured cellular foams (MCF) silica with different vanadium contents were synthesized by direct hydrothermal method, which applied as catalysts for the oxidative dehydrogenation of propane (ODP). Vanadium doping amount significantly affects the distribution and coordination environment of VOx and TiOx species on the MCF silica. With the increasing of V content, the TiOx species incorporated into silica framework were substituted by some framework V species to form more polymeric or small TiO2 nanoclusters. VOx species were incorporated on both silica surface and TiOx species surface. The interaction between highly dispersed VOx and polymerized TiO2 enhanced the C3 H6 formation rate. The 3 V5Ti/MCF catalysts showed the highest propylene productivity (4.2 kgpropylene  kgcat −1  h −1, at 500 °C) among the xV5Ti/MCF catalysts because of the highest concentration isolated/oligomeric VOx species incorporated on the appropriate polymerized TiO2 surface. Abstract : Vanadium and titanium‐incorporated mesostructured cellular foams (MCF) silica were synthesized by direct hydrothermal method, which applied as catalysts for the oxidative dehydrogenation of propane (ODP). VOx species were incorporated on both silica surface and TiOx species surface. The interaction between highly dispersed VOx and polymerized TiO2 enhanced the C3 H6 formation rate. The 3 V5Ti/MCF catalysts showed the highest propylene productivity among the xV5Ti/MCF catalysts because of the highest concentration isolated/oligomeric VOx species incorporated on the appropriate polymerized TiO2 surface.